Lost Salt Technique for Fabrication of Closed Hollow Bulb Obturator in Maxillectomy: A Case Report - Joshi, S; Basnet, BB; Parajuli, PK; Suwal, P (Journal of Nepalese Prosthodontic Society, 2024)
Maxillectomy defects can result in oroantral communication leading to difficulty in swallowing, deglutition, impaired speech and not to mention the resultant facial disfigurement. Prosthetic rehabilitation of such defects is often challenging due to the extent of the defect area along with the absence of adequate retention caused by the size and weight of the prosthesis. To fabricate a lightweight prosthesis, an open hollow obturator or a closed hollow obturator is usually chosen. This case report describes a simple and one step fabrication of a closed hollow bulb obturator using the traditional lost salt technique in a patient with maxillectomy.